2014
DOI: 10.4103/0970-1591.126909
|View full text |Cite
|
Sign up to set email alerts
|

BPH and prostate cancer risk

Abstract: Introduction:With the exclusion of non-melanomatous skin malignancy, prostate cancer (PCa) is the second most prevalent cancer in men globally. It has been reported that the majority of men will develop benign prostatic hyperplasia (BPH) by the time they reach their 60s. Together, these prostatic diseases have a significant morbidity and mortality affecting over a billion men throughout the world. The risk of developing prostate cancer of men suffering BPH is one that has resulted in a healthy debate amongst t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 30 publications
2
42
0
2
Order By: Relevance
“…About 20% of the prostate adenocarcinoma is found incidentally in a histopatological procedure for examining the prostate gland based on the indication of hyperplasia. 3 Adenocarcinoma prostate showed a high morbidity and mortality with a number of 234.460 diagnosed and 27.350 passed away after diagnosed. 4 A study found more than 230.000 new cases and 30.000 of them was death.…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of the prostate adenocarcinoma is found incidentally in a histopatological procedure for examining the prostate gland based on the indication of hyperplasia. 3 Adenocarcinoma prostate showed a high morbidity and mortality with a number of 234.460 diagnosed and 27.350 passed away after diagnosed. 4 A study found more than 230.000 new cases and 30.000 of them was death.…”
Section: Introductionmentioning
confidence: 99%
“…К его значи-мым компонентам относят протеинкиназы AKT, m-TOR, PTEN и др. Известно, что мужчины с доброкачественной гиперплазией предстательной железы (ДГПЖ) имеют больший риск развития РПЖ [10]. В настоящее время превалирует точка зрения об общности патогенетических процессов, лежащих в основе развития ДГПЖ и РПЖ [11].…”
unclassified
“…There were some studies that confirm validity of this study. Carter et al [11], showed that 50% of men between 70 and 80 years of age showed histological evidence of malignancy. At that time risk of 42% for developing histological evidence of prostate cancer in 50-year-old men had been calculated.…”
Section: Discussion Of Resultsmentioning
confidence: 99%